ANALISIS KINERJA PORTOFOLIO SAHAM BERBASIS METODE SHARPE, TREYNOR, DAN JENSEN UNTUK KESEHATAN INVESTASI SAHAM (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2018) - Endang Utami Aprilia Musiin; Anik Malikah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study uses a single index method using the ratio of Sharpe, Treynor, and Jensen to see the performance of stock portfolios. The sample in this study were 49 manufacturing companies listed on the Indonesia Stock Exchange during the period 2014-2018. Based on the calculation using the Sharpe method it was found that the best portfolio performance during the 2014-2018 research period was DLTA and the Lowest Performance during 2014-2018 was WIIM. The calculation results using the Treynor method showed that the best portfolio performance during the 2014-2018 research period was DLTA and the Lowest Performance during 2014-2018 was WIIM. The results of calculations using the Jensen method show that the best portfolio performance during the 2014-2018 study period was DLTA and the lowest performance during 2014-2018 was WIIM. The results of the portfolio performance comparison show that in general there are similarities between the 3 models used, namely the Sharpe, Treynor and Jensen methods. This is indicated by the similarity of ratings from the same company with the 3 calculation methods. In general the best return is obtained by DLTA with the Treynor method and the lowest performance is obtained by WIIM with the Sharpe Method.Keywords: Portfolio Performance, Sharpe, Treynor, Jensen